Delirium superimposed on dementia: a quantitative and qualitative evaluation of informal caregivers and health care staff experience - Morandi, Alessandro (J Psychosom Res, 2015)
OBJECTIVE: Delirium superimposed on dementia (DSD) is common and potentially distressing for patients, caregivers, and health care staff. We quantitatively and qualitatively assessed the experience of informal caregiver and staff (staff nurses, nurse aides, physical therapists) caring for patients with DSD. METHODS: Caregivers’ and staff experience was evaluated three days after DSD resolution (T0) with a standardized questionnaire (quantitative interview) and open-ended questions (qualitative interview); caregivers were also evaluated at 1-month follow-up (T1). RESULTS: A total of 74 subjects were included; 33 caregivers and 41 health care staff (8 staff nurses, 20 physical therapists, 13 staff nurse aides/health care assistants). Overall, at both T0 and T1, the distress level was moderate among caregivers and mild among health care staff. Caregivers reported, at both T0 and T1, higher distress related to deficits of sustained attention and orientation, hypokinesia/psychomotor retardation, incoherence and delusions. The distress of health care staff related to each specific item of the Delirium-O-Meter was relatively low except for the physical therapists who reported higher level of distress on deficits of sustained/shifting attention and orientation, apathy, hypokinesia/psychomotor retardation, incoherence, delusion, hallucinations, anxiety/fear. The qualitative evaluation identified important categories of caregivers ‘and staff feelings related to the delirium experience. CONCLUSIONS: This study provides information on the implication of the experience of delirium on caregivers and staff. The distress related to DSD underlines the importance of providing continuous training, support and experience for both the caregivers and health care staff to improve the care of patients with delirium superimposed on dementia.